Teaching Irregular Verbs through Crossword Puzzle in the Second Semester of the Seventh Grade Students of East Lampung Junior High - Yuspik, Yuspik; Dwiono, Rija; Hariyanto, Hariyanto; Mar’an, Desy Awal (JADEs Journal of Academia in English Education, 2023)
This research investigated the process of teaching irregular verbs using crossword puzzles to second-semester eleventh-grade students of SMP N 1 Gunung Pelindung Lampung Timur in the 2022/2023 academic year. The researcher believed that this technique could help students learn irregular verbs more effectively. The research was descriptive qualitative research, and the population was the second-semester seventh-grade students of SMP N 1 Gunung Pelindung Lampung Timur. The researcher used purposive sampling to select the sample, choosing class VII C, which consisted of 28 students and 1 English teacher. Data collection techniques included observation, interviews, and questionnaires. The data analysis showed that the teaching and learning process using crossword puzzles ran well. It was a good technique that could be implemented in the process of teaching and learning English vocabulary, especially irregular verbs. Moreover, crossword puzzles were not only easy for teachers and students to implement, but they could also increase student motivation and participation in the teaching and learning process. In conclusion, the research found that using crossword puzzles to teach irregular verbs was an effective and efficient method. It was a fun and engaging activity that could help students learn and remember irregular verbs more easily.